Determinants of Customer Service Quality on Hotel Guest Satisfaction in the Samosir Tourism Area with a Structural Equation Modeling Approach - Yossie Rossanty; Muhammad Dharma Tuah Putra Nasution; Irawan Irawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study is to test the determinants of service quality aspects of Reliability, Responsiveness, Assurance, Empathy and Tangibles on the satisfaction of hotel tourists in the Samosir area. This research test tool using the Structural Equation Modeling model. The results prove that the structural model Reliability to Costomer Satisfaction is significant, meaning that reliability has a significant effect on Costomer Satisfaction. Responsivenes structural model to Costomer Satisfaction is significant, meaning that responsiveness has a significant effect on Costomer Satisfaction. Structural model assurance for Costomer Satisfaction is significant, meaning that assurance has a significant effect on Costomer Satisfaction. The structural model of empathy for Costomer Satisfaction is significant, meaning that empathy has a significant effect on Costomer Satisfaction. Tangibless structural model to Costomer Satisfaction is insignificant, meaning that tangibless has no significant effect on Costomer Satisfaction. Structural model assurance for Costomer Satisfaction is significant, meaning that assurance has a significant effect on Costomer Satisfaction. The structural model of empathy for Costomer Satisfaction is significant, meaning that empathy has a significant effect on Costomer Satisfaction. Tangibless structural model to Costomer Satisfaction is insignificant, meaning that tangibless has no significant effect on Costomer Satisfaction. Structural model assurance for Costomer Satisfaction is significant, meaning that assurance has a significant effect on Costomer Satisfaction. The structural model of empathy for Costomer Satisfaction is significant, meaning that empathy has a significant effect on Costomer Satisfaction. Tangibless structural model to Costomer Satisfaction is insignificant, meaning that tangibless has no significant effect on Costomer Satisfaction.